2004
DOI: 10.1007/978-3-540-30136-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Liver Motion Due to Needle Pressure, Cardiac, and Respiratory Motion During the TIPS Procedure

Abstract: Abstract. TIPS (Transjugular Intrahepatic Portosystemic Shunt) is an effective treatment for portal hypertension. However, during the procedure, respiration, needle pressure, and possibly other factors cause the liver to move. This complicates the procedure since the portal vein is not visible during needle insertion. We present the results of a study of intraoperative liver motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The challenge is that, because of breathing, needle pressure and heartbeat, the liver moves as the needle is guided through the target. Therefore, a real-time registration is performed by tracking an ovoid balloon catheter lodged in the hepatic vein and its movement is used to estimate the movement of the liver's vessels [11]. In the context of this project, it is critical to initialize the position and orientation of the 3-dimensional vascular model with respect to the balloon, prior to any tracking.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge is that, because of breathing, needle pressure and heartbeat, the liver moves as the needle is guided through the target. Therefore, a real-time registration is performed by tracking an ovoid balloon catheter lodged in the hepatic vein and its movement is used to estimate the movement of the liver's vessels [11]. In the context of this project, it is critical to initialize the position and orientation of the 3-dimensional vascular model with respect to the balloon, prior to any tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Motion is predominantly in the rostro-caudal (head to foot) direction, but movement of several millimeters occurs along the other two axes as well (Venkatraman et al, 2004). Cardiac motion contributes less to liver motion than does respiration, but cardiac motion may produce displacements of 1- 2 millimeters predominantly in the lateral direction (Venkatraman et al, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Throughout the procedure, real-time image acquisition with MR protocols optimized for feature tracking are collected for motion compensation. It has been shown that liver motion is primarily due to respiration and has dominant motion components in the cranial-caudal and anterior-posterior directions and less motion in the left-right direction [4,5,6]. While the liver mostly behaves as a rigid body [7,8], non-rigid motion is non-negligible [5] and should be handled for accurate target tracking.…”
Section: Methodsmentioning
confidence: 99%